Ocular surface changes in long-term soft contact lens wearing. Treatment approach - I.A. Bubnova; G.B. Egorova (РМЖ "Клиническая офтальмология")
I.A. Bubnova, G.B. Egorova Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Soft contact lens fitting and wearing require the choice of the most appropriate contact lens parameters considering external factors and patient’s needs. Breaking one or several conditions may alter normal eye physiology in terms of both functions and anatomy and result in contact lens induced dry eye. Currently, there are numerous agents to prevent tear film instability and to improve ocular surface. Preservative-free hyaluronic acid-containing tear substitutes of low viscosity are recommended to prevent ocular discomfort in eyes wearing soft contact lenses. In eye dryness and tear film instability, hyaluronic acid product containing vitamin B12 (which provides antioxidant protection) is recommended. When the effect of tear substitutes of low viscosity is scarce, 5% dexpanthenol gel-containing product is recommended to treat superficial corneal abrasions and to improve epithelial healing. Key words: soft contact lenses, dry eye, tear film, hyaluronic acid, dexpanthenol, Artelac, Corneregel. For citation: Bubnova I.A., Egorova G.B. Ocular surface changes in long-term soft contact lens wearing. Treatment approach. Russian Journal of Clinical Ophthalmology. 2019;19(1):32–36. About the authors: Bubnova Irina Alekseevna — MD, PhD, Senior Scientist of the Department of Refractive Disorders; Egorova Galina Borisovna — MD, PhD, Chief Scientist of the Department of Refractive Disorders. Scientific Research Institute of Eye Diseases. 11a, Rossolimo str., Moscow, 119021, Russian Federation. Contact information: Irina A. Bubnova, e-mail: bubnovai@mail.ru. Financial Disclosure: no authors have a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 02.11.2018.